The legal and economic aspects of commercial information based on the Act on Rendering Electronic Services of 18 July 2002 - Smus, Tomasz R. (Prawne i ekonomiczne aspekty informacji handlowej w świetle ustawy o świadczeniu usług drogą elektroniczną z dnia 18 lipca 2002 roku, 2011)
The article presents the origin of the Act on Rendering Electronic Services of 18 July 2002. The draft of the Act as well as the problems of the electronics trade and its regulation are discussed. The legal aspects of commercial information with reference to certain economic elements are presented in detail
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 157-170
Keywords: rendering electronic services; commercial information; legal and economic aspects of commercial information; advertising; promotion